2007
DOI: 10.1051/0004-6361:20066514
|View full text |Cite
|
Sign up to set email alerts
|

The UKIRT wide-field camera

Abstract: Context. The infrared wide-field camera (WFCAM) is now in operation on the 3.8 m UK Infrared Telescope on Mauna Kea. WFCAM currently has the fastest survey speed of any infrared camera in the world, and combined with generous allocations of telescope time, will produce deep maps of the sky from Z to K band. The data from a set of public surveys, known as UKIDSS, will be initially available to astronomers in ESO member states, and later to the world. Aims. In order to maximise survey speed, the WFCAM field of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
514
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 597 publications
(521 citation statements)
references
References 14 publications
1
514
0
Order By: Relevance
“…Based Lawrence et al (2007). UKIDSS uses the UKIRT Wide Field Camera (WFCAM; Casali et al 2007). The photometric system is described in Hewett et al (2006), and the calibration is described in Hodgkin et al (2009).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Based Lawrence et al (2007). UKIDSS uses the UKIRT Wide Field Camera (WFCAM; Casali et al 2007). The photometric system is described in Hewett et al (2006), and the calibration is described in Hodgkin et al (2009).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The approximate flux limits of the AO13 portion of the Stripe 82X survey are 2.2×10 −15 erg s −1 cm −2 , 1.3×10 −14 erg s −1 cm −2 , and 6.7×10 −15 erg s −1 cm −2 , in the soft (0.5-2 keV), hard (2-10 keV), and full (0.5-10 keV) bands. From matching the X-ray source list to available multiwavelength catalogs, including SDSS (Ahn et al 2012;Jiang et al 2014), WISE (Wright et al 2010;Mainzer et al 2011), UKIDSS (Hewett et al 2006;Casali et al 2007;Lawrence et al 2007;Warren et al 2007), VHS (McMahon et al 2013), GALEX (Morrissey et al 2007), FIRST Helfand et al 2015), and Herschel (Viero et al 2014), we identified reliable counterparts for 93% of the sample. About 29% of the X-ray sources are classified via spectroscopic redshifts.…”
Section: Resultsmentioning
confidence: 95%
“…We searched for counterparts to the XMM-Newton AO13 sources in publicly available multi-wavelength databases: SDSS, WISE (Wright et al 2010), UKIDSS (Hewett et al 2006;Casali et al 2007;Lawrence et al 2007), VHS (McMahon et al 2013), GALEX (Morrissey et al 2007), FIRST, and the Herschel Survey of Stripe 82 (HerS; Viero et al 2014). To determine whether a multi-wavelength association to an X-ray source represents the true astrophysical counterpart rather than a chance coincidence, we use the maximum likelihood estimator method (MLE; Sutherland & Saunders 1992) to match between the X-ray source lists and the ancillary catalogs.…”
Section: Multi-wavelength Catalog Matchingmentioning
confidence: 99%
See 2 more Smart Citations